Changes in Transepidermal Water Loss and Skin Hydration according to Expression of Aquaporin-3 in Psoriasis - Lee, Young (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2012)
BACKGROUND: Aquaporins (AQPs) are a family of water transporting proteins present in many mammalian epithelial and endothelial cell types. Among the AQPs, AQP3 is known to be a water/glycerol transporter expressed in human skin. OBJECTIVE: The relationship between the expression level of AQP3 and transpidermal water loss (TEWL) in the lesional and peri-lesional skin of psoriasis-affected patients, and skin hydration in the lesional and peri-lesional skin of psoriasis patients, was investigated. METHODS: The expression of AQP3 in psoriasis-affected and healthy control skin was determined using immunohistochemical and immunofluroscence staining. TEWL and skin hydration were measured using a Tewameter® TM210 (Courage & Khazaka, Cologne, Germany) and a Corneometer® CM 820 (Courage & Khazaka), respectively. RESULTS: AQP3 was mainly expressed in the plasma membrane of stratum corneum and the stratum spinosum in normal epidermis. Unlike the normal epidermis, AQP3 showed decreased expression in the lesional and peri-lesional epidermis of psoriasis. TEWL was increased, and skin hydration was decreased, in the lesional and peri-lesional skin of psoriasis patients, compared with the healthy control sample. CONCLUSION: Although various factors contribute to reduced skin hydration in the lesional and peri-lesional skin of psoriasis, AQP3 appears to be a key factor in the skin dehydration of psoriasis-affected skin.